Treatment of syncroneous triple genitourinary tumor with laparoscopic nephroureterectomy and conventional radical cystoprostatectomy - (:unkn) unknown (My University, 2009)
Synchronous triple primary tumor occurring in the kidney, urinary bladder and prostate is a very rare condition in the practice of Urology. We have reported combined laparoscopic nephrouretereetomy with a standard open radical cystoprostatectomy as an effective and reliable operation technique in patients with triple genitourinary tumors and high-risk co-morbidities.
Keywords: Laparoscopy; Treatment; Triple tumor